Parenteral immunization with a cyclic guanosine monophosphate-adenosine monophosphate (cGAMP) adjuvanted Helicobacter pylori vaccine induces protective immunity against H. pylori infection in mice - Jing Chen; Youxiu Zhong; Yu Liu; Chongfa Tang; Yanbin Zhang; Bo Wei; Wangxue Chen; Meiying Liu (Taylor & Francis Group, 2020)
Under the trend of antibiotic resistance of H. pylori leading to the decrease of eradication rate, the development of a vaccine is the best choice to fight against H. pylori. In this study, we attempted to reduce the amounts of required antigens by using three different parenteral routes of immunization and an adjuvant cGAMP (cyclic guanosine monophosphate-adenosine monophosphate) to enhance the immunogenicity of the vaccine candidate. The immune protection and post-challenge immune responses were assessed and compared in mice immunized with recombinant Helicobacter pylori urease A, urease B, and neutrophil-activating protein adjuvanted with cGAMP. The gastric mucosal colonization by H. pylori was significantly reduced in mice immunized by intranasal and, to a less degree, subcutaneous route, but not by intramuscular route. All immunized mice, regardless of the route of immunization, displayed significant, but comparable, increases in antigen-specific serum IgG and mucosal IgA responses 5 weeks post-challenge. The magnitude of the vaccine-induced protection appeared to be associated with the level of antigen-specific Th1 and particularly Th17 responses, as IL-17 responses were only detected in intranasally immunized mice. Taken together, we explored and confirmed the possibility of using a novel adjuvant (cGAMP) to induce significant protective immunity with 10% of oral vaccine antigen dosage through parenteral immunization, especially intranasal immunization. This may provide an alternative approach to oral immunization for the development of effective H. pylori vaccines.